Structure-activity relationship and salinity-driven degradation pathway and toxicity divergence of bromophenols during advanced reduction in VUV/sulfite system - Yawei Shi; Keyan Liu; Yan Wang; Ya Sun; Zonglin Pan; Mengqi Li; Guanghui Ding (Journal of Water Process Engineering, 2026)

Regulatory effects of Annulohypoxylon stygium metabolites on the dimorphic transition of Tremella fuciformis - Haichen Huang; Lingli Wei; Jialan Zheng; Shuyu Xing; Yingqi Tang; Silong Chen; Keyan Shen; Jianqiu Chen; Shujing Sun (Food Bioscience, 2026)

Three-Dimensional Mineral Prospectivity Mapping by a Gradient Boosting-Based Integrated Learning Method with Data Representation Adaptability: A Case Study of the Haopinggou Gold Polymetallic Deposit, China - Mingjing Fan; Keyan Xiao; Li Sun; Nan Li; Yang Xu; Wenjie Li (Natural Resources Research, 2026)

Microbial adaptation and environmental co-selection drive antimicrobial resistance risk in agricultural ditches, evidence from the multilevel ditch-river continuum - Xiangyao Wu; Yulin Qi; Lingchen Meng; Keyan Li; Chao Ma; Dietrich A. Volmer; Chunmei Chen; Peizhe Sun; Pingqing Fu; Zhifeng Yan (Journal of Hazardous Materials, 2026)

Single-tube duplex isothermal amplification assay for rapid detection of pistachio and cashew allergens - Ruifeng Mao; Yuwen Zhou; Xinru Zhan; Miqi Tan; Yue Sun; Yuanmeng Dong; Keyan Yuan; Yingying Chen; Wei Wang; Dengchao Li; Enjie Diao (Food Control, 2026)

Achieving carrier migration pathway transformation to enhance photocatalytic moxifloxacin degradation activity by regulating the Fermi Level of g-C3N4/ ZnIn2S4 through sulfur vacancies - Han Sun; Yonghao Dong; Lei Wang; Xudong Wang; Junwei Xin; Jie Ren; Ruosong Jing; Jiayuan Yan; Yichun Xue; Keyan Zhao (Journal of Environmental Chemical Engineering, 2025)

MnFe2O4 coupled with MgAl-LDH for activation of periodate towards enhanced degradation of organic pollutants in water - Ya Sun; Chang Ma; Yawei Shi; Zonglin Pan; Yumei Xing; Yan Wang; Keyan Liu; Guanghui Ding (Journal of Water Process Engineering, 2025)

The first temperature reconstruction based on tree-ring blue intensity in the Qinling Mountains - Mei Xie; Qiufang Cai; Yu Liu; Keyan Fang; Qiuyue Zhou; Meng Ren; Kebayier Meng; Qiang Li; Changfeng Sun; Huiming Song; Dan Chen; Yufei Chen (Dendrochronologia, 2025)

Flexible MXene-functionalized composite phase change film with dual-mode of solar-thermal conversion and infrared stealth - Keyan Sun; Fanmu Meng; Xinyu Zhang; Huimin Yan; Hanqing Liu; Quan Shi (Chemical Engineering Journal, 2025)

Probabilistic Health Risk Assessment and Grading Benchmark Estimation of Atmospheric PM2.5-Bound Heavy Metals in China - Wei Huang; Weilian Sun; Chifei Zhou; Keyan Long; Zunzhen Zhang (Archives of Environmental Contamination and Toxicology, 2025)

Boosting chlorobenzene oxidation over MIL-101(Cr) derived CrOx catalysts: The stepwise regulation of CrOx clusters and oxygen species by calcination atmospheres - Boqiong Jiang; Jun Liu; Keyan Wei; Hanfeng Lu; Xiaole Weng; Jingyi Han; Yi Zhang; Shaocai Yu; Yuhai Sun (Journal of Hazardous Materials, 2025)

YTHDF2 phase separation promotes arsenic-induced keratinocyte transformation in a poly-m6A-dependent manner by inhibiting translational initiation of the key tumor suppressor PTEN - Tianhe Zhao; Wenxiao Xiong; Jingsilin Cai; Qian Zhang; Donglei Sun; Keyan Long; Jin Man; Zunzhen Zhang (Journal of Hazardous Materials, 2024)

Study on exploring the extraction of geological elements from 3D geological models within the constraints of geological knowledge - Guangjun Ji; Zizhao Cai; Yan Lu; Jixiang Zhu; Keyan Xiao; Li Sun (Computers & Geosciences, 2024)

Deciphering the transfer of hydroclimate signals to tree-ring δ18O using a proxy system model in East Asia's Meiyu region - Yesi Zhao; Huayu Lu; Keyan Fang; Peng Zhang; Deliang Chen; Achim Bräuning; Jussi Grießinger; Bao Yang; Chenghong Liang; Hongyan Zhang; Yiqian Sun; Qing Jin; et al. (Chemical Geology, 2024)

Reactive transport numerical modeling of intermediate sulfidation epithermal deposit: A case study of Haopinggou Ag-Au-Pb-Zn deposit, Henan province, China - Cheng Chang; Keyan Xiao; Guanhong Feng; Li Sun; Junsheng Yang (Journal of Geochemical Exploration, 2024)

Particle-size correlation and prediction models of atmospheric heavy metals - Wei Huang; Weilian Sun; Donglei Sun; Chifei Zhou; Keyan Long; Zunzhen Zhang (Atmospheric Environment, 2024)

Influence of different tectonic settings on fracture formation and fluid flow around upper-crustal magmatic intrusion: insights from numerical modelling - Cheng Chang; Keyan Xiao; Gang Luo; Li Sun (Earth Science Informatics, 2024)
Large porphyry Cu and epithermal Au deposits tend to form in distinct tectonic, porphyry and high-sulfidation epithermal deposits in compressional settings, and low-sulfidation epithermal deposits in extensional settings. Given that the analysis of the shallow metallogenic dynamic processes at the upper-crust scale is insufficient, especially the ore-bearing fracture formation and fluid-focusing mechanism around the mineralizing magmatic intrusion under different tectonic backgrounds, we aimed to study how tectonic settings influence fracture formation and fluid hydrodynamics in and around a hot intrusion. We developed a finite element model coupling thermal-hydrological-mechanical processes to simulate the fracture formation, evolution of fluid velocities, and accumulation of water-rock interactions. The model results show that tectonic compression increases the degree of fracturing, hydrothermal fluid velocities, and water-rock interaction within and laterally around the intrusion; tectonic extension enhances fracturing, hydrothermal fluid velocities, and water-rock interaction at shallow depth. These results confirm that tectonic compression may promote the formation of porphyry Cu deposits, while tectonic extension may promote the formation of shallow hydrothermal deposits. Our model explains the effects of tectonic activity on fracture formation and fluid flow around hot magmatic intrusions in upper crust and deepens our understanding of the relationship between tectonic activity and deposit formation there.

Importance of forest stand structures for gross rainfall partitioning on China’s Loess Plateau - Xu Hu; Zhaoqi Fu; Ge Sun; Biao Wang; Keyan Liu; Churui Zhang; Lu Han; Lixin Chen; Zhiqiang Zhang (Journal of Hydrology, 2024)

N6-methyladenosine promotes aberrant redox homeostasis required for arsenic carcinogenesis by controlling the adaptation of key antioxidant enzymes - Tianhe Zhao; Donglei Sun; Keyan Long; Wenxiao Xiong; Jin Man; Qian Zhang; Zunzhen Zhang (Journal of Hazardous Materials, 2024)

Oxidative Stress Induced by Arsenite is Involved in YTHDF2 Phase Separation - Jin Man; Qian Zhang; Tianhe Zhao; Donglei Sun; Weilian Sun; Keyan Long; Zunzhen Zhang (Biological Trace Element Research, 2024)

Spatial–temporal distribution and source analysis of atmospheric particulate-bound cadmium from 1998 to 2021 in China - Wei Huang; Donglei Sun; Tianhe Zhao; Keyan Long; Zunzhen Zhang (Environmental Geochemistry and Health, 2024)

Revisiting the natural resources-financial development nexus in China: The importance of economic policy uncertainty - Yizhong Sun; Keyan Jin; Deyong Wang; Qingyang Wu; Zhezhou Li (Resources Policy, 2023)

N6-methyladenosine upregulates ribosome biogenesis in environmental carcinogenesis - Tianhe Zhao; Donglei Sun; Keyan Long; Bernardo Lemos; Qian Zhang; Jin Man; Manyu Zhao; Zunzhen Zhang (Science of The Total Environment, 2023)

ZYY-B-2, a novel ALK inhibitor, overcomes resistance to ceritinib by inhibiting P-gp function and induces apoptosis through mitochondrial pathway in ceritinib-resistant H2228 cells - Ying Gao; Tong Liu; Jingang Liu; Yuying Yang; Keyan Sun; Zengqiang Li; Xin Zhai; Daiying Zuo (Chemico-Biological Interactions, 2023)

Mechanism of the reduced allergenicity of shrimp (Macrobrachium nipponense) by combined thermal/pressure processing: Insight into variations in protein structure, gastrointestinal digestion and immunodominant linear epitopes - Kexin Liu; Songyi Lin; Yao Liu; Shan Wang; Qiaozhen Liu; Keyan Sun; Na Sun (Food Chemistry, 2023)

Priming of rice defense against a sap-sucking insect pest brown planthopper by silicon - Yibin Lin; Xianhui Lin; Chaohui Ding; Ming Xia; Rongrong Xue; Zhongxiang Sun; Daoqian Chen; Keyan Zhu-Salzman; Rensen Zeng; Yuanyuan Song (Journal of Pest Science, 2022)

Geochemically Constrained Prospectivity Mapping Aided by Unsupervised Cluster Analysis - Shuai Zhang; Emmanuel John M. Carranza; Keyan Xiao; Zhenghui Chen; Nan Li; Hantao Wei; Jie Xiang; Li Sun; Yang Xu (Natural Resources Research, 2021)

Host-induced gene silencing of brown planthopper glutathione S-transferase gene enhances rice resistance to sap-sucking insect pests - Jun Yang; Xiao-Qin Sun; Keyan Zhu-Salzman; Qing-Ming Qin; Hui-Qiang Feng; Xiang-Dong Kong; Xu-Guo Zhou; Qing-Nian Cai (Journal of Pest Science, 2021)

Mapping and identification of CsSh5.1, a gene encoding a xyloglucan galactosyltransferase required for hypocotyl elongation in cucumber (Cucumis sativus L.) - Keyan Zhang; Junsong Pan; Yue Chen; Ying Wei; Hui Du; Jingxian Sun; Duo Lv; Haifan Wen; Huanle He; Gang Wang; Run Cai (Theoretical and Applied Genetics, 2021)

East Asian Summer Monsoon moisture sustains summer relative humidity in the southwestern Gobi Desert, China: evidence from δ18O of tree rings - Qiang Li; Yu Liu; Takeshi Nakatsuka; Keyan Fang; Huiming Song; Ruoshi Liu; Changfeng Sun; Gang Li; Ke Wang (Climate Dynamics, 2019)

Pea aphid promotes amino acid metabolism both in M edicago truncatula and bacteriocytes to favor aphid population growth under elevated CO 2 - Huijuan Guo; Yucheng Sun; Yuefei Li; Bin Tong; Marvin Harris; Keyan Zhu‐Salzman; Feng Ge (Global Change Biology, 2013)
Rising atmospheric CO 2 levels can dilute the nitrogen ( N ) resource in plant tissue, which is disadvantageous to many herbivorous insects. Aphids appear to be an exception that warrants further study. The effects of elevated CO 2 (750 ppm vs. 390 ppm) were evaluated on N assimilation and transamination by two M edicago truncatula genotypes, a N‐fixing‐deficient mutant ( dnf1 ) and its wild‐type control (Jemalong), with and without pea aphid ( Acyrthosiphon pisum ) infestation. Elevated CO 2 increased population abundance and feeding efficiency of aphids fed on Jemalong, but reduced those on dnf1 . Without aphid infestation, elevated CO 2 increased photosynthetic rate, chlorophyll content, nodule number, biomass, and pod number for Jemalong, but only increased pod number and chlorophyll content for dnf1 . Furthermore, aphid infested Jemalong plants had enhanced activities of N assimilation‐related enzymes (glutamine synthetase, Glutamate synthase) and transamination‐related enzymes (glutamate oxalate transaminase, glutamine phenylpyruvate transaminase), which presumably increased amino acid concentration in leaves and phloem sap under elevated CO 2 . In contrast, aphid infested dnf1 plants had decreased activities of N assimilation‐related enzymes and transmination‐related enzymes and amino acid concentrations under elevated CO 2 . Furthermore, elevated CO 2 up‐regulated expression of genes relevant to amino acid metabolism in bacteriocytes of aphids associated with Jemalong, but down‐regulated those associated with dnf1 . Our results suggest that pea aphids actively elicit host responses that promote amino acid metabolism in both the host plant and in its bacteriocytes to favor the population growth of the aphid under elevated CO 2 .

Is APOE $\boldsymbol{ε}$ 3 a favourable factor for the longevity: an association study in Chinese population - JIE FENG; LEI XIANG; GANG WAN; KEYAN QI; LIANG SUN; ZEZHI HUANG; CHENGUANG ZHENG; ZEPING LV; CAIYOU HU; ZE YANG (Journal of Genetics, 2011)